(3cJGH eLeY GdSYGOGJs - (3Ydj Hf CHj WGdH GdbQTj,J (B40 (3g` s
(3ChdgG (B:s
(3Gddge jG ef OdY dSGf GdUHGM HfWb HJdLI hSQM bWY Gddjd GdeXde HZjGgH JdLdLI s
(3BNQgG (B:s
(3NGFHkG jG cQje jG QMje HQMeJc jG CQMe GdQGMejf hGdMeO ddg QH GdYGdejf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B6s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B295s
(3eUOQ GbJfGA GdCUd (B:s
(3GdOcJhQ MSjf Ydi eMahX (B_ (3HZOGO (B(198) s
Keywords: (3GdeLGejYs